How Slow should Slow Fashion be? : The Perceptions of Slow Fashion Stakeholders on the Distribution of Apparel - Schlarb, Luisa (2021)
The apparel industry is booming. Every year, 62 million tonnes of apparel are consumed globally, and shopping apparel is even considered a leisure activity. However, with reoccurring criticism of the negative impacts of the fashion industry, concepts like slow fashion are increasingly becoming mainstream as they address the increasing concern from consumers for environmental protection, social responsibility, and economic sustainability. However, research on the challenges for slow fashion companies to align their supply with product strategies is still scarce. In detail, the focus of this thesis is on the distribution of apparel depending on the demand patterns. Thus, the literature review focuses on the current research of slow fashion and which demands retailers, brands and customers have for a distribution system. Previously, the rapid change and volatile demand in the fashion industry was successfully met by fast fashion brands with an agile supply chain. However, it is questionable if this supply chain is applicable for slow fashion with the rise of ethical consumerism and its aversion to oversupply. Therefore, the focus of this Master’s Thesis is on different slow fashion stakeholders’ perceptions on the distribution of apparel to deliver more insights on this issue. The research data was collected through semi-structured interviews with 10 stakeholders of the fashion industry (brand manager, supply manager, retailers) and qualitatively analysed with Open coding. The research indicates that slow fashion stakeholders identify the NOS System and the Seasonal System as more beneficial for the slow fashion industry depending on the product strategy. In detail, interviewed slow fashion brands which aimed to offer higher quality apparel with long-term design perceived the NOS System to be more ben-eficial. Slow fashion brands which aimed to bring slow fashion to the mainstream market regard the Seasonal System to be more beneficial for the slow fashion industry.